Effect of modifications in rules in competition on participation of male youth goalkeepers in soccer - Ortega-Toro, E.; Garcia-Angulo, A.; Giménez-Egido, J.-M.; Garcia-Angulo, F. J.; Palao, J. (International Journal of Sports Science & Coaching, 2018)
he purpose of this study was to assess the effect of modifications in field size, number of players, and goal size on the goalkeeper's actions in competition in male youth soccer (n=4) (under-12). A quasi-experimental design was implemented to measure the effects of the changes in the number of players per team (8-a-side vs. 5-a-side), goal size (6×2m vs. 3×2m), and field size (58×38m vs. 38×20m) on the offensive and defensive technical and tactical actions of the goalkeeper. Four male under-12 goalkeepers (age=11.33±0.6 years, average weekly training=2.45±0.3h, and years of experience=4.8±0.9 years) were analyzed in three tournaments (8-a-side; 5-a-side; 8-a-side). The dependent variables were: defensive and offensive technical actions taken by the goalkeepers and the way their actions were carried out. The results show that in the 5-a-side soccer matches, goalkeepers carried out more defensive actions (8-a-side: 31.2±3.8; 5-a-side: 77.75±5.0; 8-a-side: 39.5±6.0; F2,6=111,218, p=.000, 2=.974; ES .998) and offensive actions (8-a-side: 58.0±7.1; 5-a-side: 84.0±13.5; 8-a-side: 58.1±9.2; F2,6=16,257, p=.004, 2=.844; ES .996) than in 8-a-side soccer matches. The reduction in field size, number of players, and goal size resulted in under-12 goalkeepers having more interaction and more variability in their actions. This information could help the different stakeholders to adapt or design the youth soccer competition rules in a way that allows goalkeepers to have more experiences.